Household water treatment practice and associated factors among households dependent on unimproved water sources in Ameya district, Oromia, Ethiopia. (5th May 2022) - Eticha, Mesfin; Geremew, Abraham; Dirirsa, Gebisa; Bayu, Kefelegn; Girma, Haileyesus; Mengistu, Dechasa Adare
Abstract: Globally, about 435 million people depend on unimproved drinking water sources, and 144 million people still rely on surface water. Specifically, a significant part of the population in Ethiopia depends on unimproved water sources. Studies have examined household water treatment practices in the country, but there is limited research regarding the population that depends on unimproved water sources. Therefore, this study aims to evaluate household water treatment practices and related factors for the households that depend on unimproved water sources in the Ameya district of the Oromia Regional State in Southwest Ethiopia. A community-based, cross-sectional study was used to assess the water treatment practices and related factors for the households that use an unimproved water source in the Ameya district of the Oromia Regional State in Ethiopia. The study used a multistage sampling technique and included a total of 413 households. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) 26 statistical package. A multivariable logistic regression was applied to identify the factors related to household water treatment practices at a 95% confidence interval (CI). Variables with a p -value of less than 0.05 in the multivariable regression were considered to be significantly related to the water treatment practice. The current study showed that 125 (30.3%) of the households that used unimproved water sources practiced household water treatment at the household level. These water treatment methods include boiling (60.8%) the water or using cloth filters (23.2%) or chlorine-based products (13.6%). When considering the training and formal education of the respondents, the water treatment practices were significantly related to the respondents' water treatment training (adjusted odds ratio (AOR) = 2.99; 95% CI 1.97–4.94) and educational status, specifically secondary education (AOR = 1.61; 95% CI 1.02–2.93). Less than one-third of the households that depend on unimproved water sources treated their water prior to drinking. Providing training to teach individuals how to treat household water is essential to improving water treatment practices. HIGHLIGHTS: About 30.3% of households practiced water treatment at the household level. Factors associated with the household level water treatment practice include educational status (being in secondary school) and training in water treatment. Improving access to information and increasing public awareness of unsafe water through the health extension worker is essential. Graphical Abstract